An introduction to modern astrophysics - Carroll, Bradley W. (Pearson Addison-Wesley, 2007)
The celestial sphere -- Celestial mechanics -- The continuous spectrum of light -- The theory of special relativity -- The interaction of light and matter -- Telescopes -- The nature of stars -- Binary systems and stellar parameters -- The classification of stellar spectra -- Stellar atmospheres -- The interiors of stars -- The sun -- The interstellar medium and star formation -- Main sequence and post-main-sequence stellar evolution -- Stellar pulsation -- The fate of massive stars -- The degenerate remnants of stars -- General relativity and black holes --Close binary star systems -- The solar system -- Physical processes in the solar system -- The terrestrial planets -- The realms of the giant planets -- Minor bodies of the solar system -- Formation of planetary systems -- Galaxies and the universe -- The milky way galaxy -- The nature of galaxies -- Galactic evolution -- The structure of the universe -- Active galaxies -- Cosmology -- The early universe